The effect of technology addiction on posture and body awareness in school age children - Razak Özdinçler, Arzu; Azim Rezaei, Derya; Şeker Abanoz, Ebru; Atay, Canan; Aslan Keleş, Yasemin; Tahran, Özge; Köroğlu, Fahri (Journal of Dependence, 2019)
Objective: The aim of our study is to investigate the frequency and duration of use of technological tools in children and to examine the relationship between the use of technological tools on posture and body awareness. Method: A total of 83 healthy children were included in the study. In addition to the demographic characteristics of children, the use and training of information technologies with communication devices, the duration and frequency of use of technological tools, the frequency of use of computers and mobile phones for different purposes were questioned. Posture evaluations were made with the New York Posture Analysis Scale. Results: The frequency of technological tools / internet usage of the participants was mobile phone (55.4%), notebook (28.9%), tablet (77.1), desktop computer (42.1%) and Internet (92.8%). The relationship between daily use of posture and posture of different technological tools was correlated only with the use of desktop computer. Conclusion: Our results show that technological tools and internet are widely used in children. Children have fewer years of use of technological tools. The effects of technology dependence on musculoskeletal system should be further investigated.